Surface Potential of MIBC at Air/Water Interface: a Molecular Dynamics Study - Phan, Chi; Nakahara, H.; Shibata, O.; Moroi, Y.; Nguyen, Van Cuong; Chaudhary, Deeptangshu (The Surface Science Society of Japan, 2012)
The interfacial behavior of alcohols is significantly different from bulk due to amphiphilic structures. Such behavior can dramatically change the interfacial properties within the nano-scale of interfacial layer and have significant applications in industrial processes such as mineral flotation. In this study, the adsorption of MIBC (methyl isobutyl carbinol), a popular frother, was investigated by molecular dynamics. Surface potential was obtained at different surface concentration and compared to experimental data. The simulations results compared well with theoretical data using a single adjustable parameter. It has been found that the disordered water molecules contribute to surface potential more than MIBC molecules. The study demonstrates the application of MD in investigating the efficiency of frother systems.